Designing in Architecture: Behavioral Approach Methodology - Astuti Indriyati, Sri; ., . (International Journal of Engineering and Technology, 2018)
A fundamental premise on environmental and behavioral fields involves assumptions about the systematic interrelationships between architecture and patterns of human behavior. The case study conducted was to confirm the needs of specific design methodology in relations to the area of Perception and Human Behavior. The research focused to the extent to which Office Space Performance gives impact on Employee Productivity and Satisfaction. Following that, It was also seen how those affect the behavior of coping. The findings show that there is a significant impact of Spacesâ€™ Performances on Space Satisfaction. Further, there is a significant impact of Space Satisfaction on Coping Behavior and also a significant impact of Spacesâ€™ Performances against Coping behavior. Humanist architecture with architectural behavior approach is required as a Concept of Planning and Architectural Design in the Future. A New Guidelines for Planning and Architectural Design Method for Architectural Design with Behavior concerns is proposed.Â Â Â